A graphene/carbon black nanofluidic membrane with fast ion transport for enhanced electrokinetic energy generation. (February 2023) - Zhang, Rong-You; Gao, Mengyao; Liu, Wei-Ren; Chiang, Wei-Hung; Yeh, Li-Hsien
Abstract: Harvesting energy from transport of water and ions at ambient environment is promising towards sustainable perspective, yet an easy-fabrication and high-performance water-enabled energy generation device remains largely unexplored. Herein, we report a simple method to fabricate a 2D/0D graphene/carbon black (GCB) nanofluidic membrane for high-performance electrokinetic energy generation (EKEG), driven by capillary action and water evaporation. The results obtained suggest that the GCB membrane features enhanced ion transport, owing to the synergistic effects of horizontally oriented 2D confined channels, highly conductive graphene, and high surface charge of GCB. Therefore, dropping 100 μL of natural seawater on one side of a GCB nanofluidic membrane is capable of achieving a considerable current of ∼121 μA and a voltage of ∼0.49 V at ambient environment (25 ± 1 °C and 55 ± 5% relative humidity), surpassing the state-of-the-art evaporation-driven EKEG devices. More amazingly, connecting ten GCB membranes in parallel can produce an ultrahigh current at the mA level. Applications in lighting up various colors of light-emitting diodes and powering electronics are demonstrated as well. This work paves new avenues for next-generation high-performance water-enabled electrokinetic energy generators. Graphical abstract: Image 1 Highlights: A 2D/0D graphene/carbon black (GCB) nanofluidic membrane has been exploited. Confined 2D conductive nanochannels endow the GCB membrane with fast ion transport. Continuous outputs of current and voltage are realized with few drops of water. A considerable current of 121 μA and voltage of 0.49 V are achieved with seawater. Ten GCB membranes in parallel can achieve the current at amazing mA level.